Dispute Resolution Under Wto Rules (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The topic of Uzbekistan's accession to the WTO is extremely important and relevant for Uzbekistan today. The existence of a mechanism for resolving international trade disputes within the framework of the World Trade Organization (WTO) is one of the most significant advantages of this organization and is important not only from an economic but also from a political point of view. Throughout the existence of the WTO the universal dispute resolution mechanism, it has been possible to achieve greater transparency in the application of rules, create a precedent base and enable countries to defend their positions on the application of trade policy measures based on a generally recognized mechanism.